2022
DOI: 10.1186/s13089-022-00259-5
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiocentesis: ultrasound guidance is essential

Abstract: Background Pericardial effusion is a common entity which may have important implications in patient’s prognosis. In several cases, pericardiocentesis is indicated for diagnostic and/or therapeutic purposes. Case presentation A blind pericardiocentesis failed in a 95-year-old woman admitted to the emergency department with a large pericardial effusion incidentally diagnosed in the ambulatory setting. Ultrasound-guided pericardiocentesis aided in eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Multiple studies and expert opinions have indicated decreased mortality and morbidity of pericardiocentesis with ultrasound guidance. 5 In the setting of extensive pneumopericardium and subcutaneous emphysema, ultrasound guidance may prove difficult. This may be due in part to the difficulty of discerning the air‐filled pericardium from pulmonary tissue, as well as the acuity of the condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies and expert opinions have indicated decreased mortality and morbidity of pericardiocentesis with ultrasound guidance. 5 In the setting of extensive pneumopericardium and subcutaneous emphysema, ultrasound guidance may prove difficult. This may be due in part to the difficulty of discerning the air‐filled pericardium from pulmonary tissue, as well as the acuity of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ultrasound‐guided pericardiocentesis is preferred over landmark‐guided methods. Multiple studies and expert opinions have indicated decreased mortality and morbidity of pericardiocentesis with ultrasound guidance 5 . In the setting of extensive pneumopericardium and subcutaneous emphysema, ultrasound guidance may prove difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusion is defined as the abnormal accumulation of fluid in the pericardial cavity, which can develop due to overproduction of pericardial fluid, decreased reabsorption, or an imbalance between the hydrostatic and oncotic pressures of the fluid [ 3 ]. There are multiple causes for the development of pericardial effusion such as heart failure, trauma, neoplasms, infections, connective tissue diseases, and metabolic disorders [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…
the hydrostatic and oncotic pressures of the fluid [3]. There are multiple causes for the development of pericardial effusion such as heart failure, trauma, neoplasms, infections, connective tissue diseases, and metabolic disorders [4].Pericardial effusion, depending on its volume and time of onset, can lead to increased intrapericardial pressures transmitted to the cardiac cavities, leading to hemodynamic alterations and in severe cases, being associated with shock, a condition known as cardiac tamponade [5,6]. The diagnosis of pericardial effusion is clinical, supported by echocardiographic findings suggesting alterations in intracardiac filling pressures.
…”
mentioning
confidence: 99%
“…1 Currently, ultrasound-guided pericardiocentesis is the recommended practice for hemodynamically significant pericardial effusion. 2 Reported procedural morbidity and mortality associated with pericardiocentesis are 1-3% and 1% respectively. 3 Cardiac chamber perforation is one of the most feared complications of pericardiocentesis.…”
Section: Introductionmentioning
confidence: 99%